The prevalence of and predictors to indicate bilateral venous duplex ultrasound testing to detect contralateral asymptomatic lower extremity deep venous thrombosis in patients with acute symptomatic lower extremity deep venous thrombosis Presented at the 2015 Vascular Annual Meeting of the Society for Vascular Surgery, Chicago, Ill, June 17-20, 2015. - Sobreira, Marcone Lima [UNESP]; Bertanha, Matheus [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Pimenta, Bárbara [UNESP]; De Oliveira Mariúba, Jamil Victor [UNESP]; Farres Pimenta, Rafael Elias [UNESP]; Yoshida, Winston Bonetti [UNESP]; Rollo, Hamilton Almeida [UNESP] (Elsevier, 2016)
Objective The goal of this study was to determine the prevalence of and predictors to indicate bilateral venous duplex ultrasound (DU) to detect contralateral asymptomatic deep venous thrombosis (DVT) in patients with acute symptomatic lower extremity DVT. Methods Venous DU reports along with medical records of the patients were collected from February 2005 to April 2012 in a tertiary university hospital in Botucatu, Brazil. All patients with DVT detected in one lower extremity routinely underwent contralateral limb venous DU examination. Exclusion criteria were previous DVT in the contralateral asymptomatic limb, thrombophlebitis, workup for pulmonary embolism, and bilateral symptomatic lower extremities. Results Scans were done in 579 patients to rule out contralateral lower extremity DVT whenever DVT was confirmed in the ipsilateral lower extremity; of these, 108 patients (18.6%) had an abnormal finding on DU examination for DVT in the contralateral limb, which was proximal DVT in 71.5%. Age >60 years (odds ratio [OR], 3.33; 95% confidence interval [CI], 1.447-7.670), malignant disease (OR, 5.21; 95% CI, 1.943-14.015), and the association of trauma plus malignant disease (OR, 7.11; 95% CI, 1.640-30.863) were the main predictors. Conclusions Age >60 years, malignant disease, lower extremity trauma, inpatient status, and recent hospitalization are risk factors associated with a high incidence of asymptomatic contralateral lower extremity DVT in patients with ipsilateral lower extremity DVT. Therefore, we recommend routine performance of a venous DU examination on the contralateral lower extremity whenever these risk factors are present in patients with ipsilateral lower extremity DVT.